No impact of breast magnetic resonance imaging on 15‐year outcomes in patients with ductal carcinoma in situ or early‐stage invasive breast cancer managed with breast conservation therapy. Issue 8 (16th December 2016) - Vapiwala, Neha; Hwang, Wei‐Ting; Kushner, Carolyn J.; Schnall, Mitchell D.; Freedman, Gary M.; Solin, Lawrence J.
Abstract : BACKGROUND: For women undergoing breast conservation therapy (BCT), the added value of breast magnetic resonance imaging (MRI) at the time of initial diagnosis remains controversial. The current study was performed to determine long‐term outcomes after BCT for women with and without pretreatment breast MRI. METHODS: Between 1992 and 2001, a total of 755 women with ductal carcinoma in situ or early‐stage invasive breast cancer underwent breast‐conserving surgery (with axillary lymph node staging for invasive carcinoma) followed by definitive breast radiotherapy. Evaluation at the time of the initial diagnosis included conventional mammography in all subjects and breast MRI in 215 women (28%). Clinical, pathologic, and treatment characteristics were comparable for patients with and without breast MRI. Outcomes were determined using the Kaplan‐Meier method and compared using the log‐rank method. RESULTS: At a median follow‐up of 13.8 years, there were 49 local failures (15 women with and 34 women without breast MRI, respectively). The 15‐year local failure rates were 8% for women with and 8% for women without MRI ( P =  .59). There also were no differences noted between women with and without breast MRI with regard to 15‐year rates of overall survival (77% vs 71%; P =  .24), freedom from distant metastases (86% vs 90%; P =  .08), and contralateral breast cancer (10% vs 8%; P =  .10). Multivariate analysis demonstrated no significant impact of breast MRI on local failure ( P =  .96). CONCLUSIONS: Breast MRI during the initial evaluation for BCT appears to have no significant impact on 15‐year rates for local control, overall survival, freedom from distant metastases, or contralateral breast cancer. The routine use of pretreatment breast MRI is not indicated for patients undergoing BCT. Cancer 2017;123:1324–1332. © 2016 American Cancer Society . Abstract : Controversy exists regarding the role of breast magnetic resonance imaging in the management of patients with early‐stage breast cancer. Long‐term results from randomized data are lacking, but the findings of the current study indicate that breast magnetic resonance imaging performed at the time of initial evaluation has no significant impact on 15‐year rates of local control, overall survival, freedom from distant metastases, or contralateral breast cancer in patients undergoing breast conservation therapy.